Epidemiology of Kaposi's sarcoma in sub-Saharan Africa. (June 2022) - Motlhale, Melitah; Sitas, Freddy; Bradshaw, Debbie; Chen, Wenlong Carl; Singini, Mwiza Gideon; de Villiers, Chantal Babb; Lewis, Cathryn M.; Muchengeti, Mazvita; Waterboer, Tim; Mathew, Christopher G.; Newton, Robert; Singh, Elvira
Abstract: Kaposi's sarcoma (KS) has become a common AIDS-defining cancer in sub-Saharan Africa. Kaposi's sarcoma-associated human herpesvirus strongly modulated by HIV-related immune suppression are the principal causes of this cancer. No other risk factors have been identified as playing a strong role. HIV prevention programs and good coverage of antiretroviral therapy (ART) in developed countries resulted in a remarkable decline in HIV-KS incidence and better KS prognosis. By contrast, in sub-Saharan Africa, population ART rollout has lagged, but clinical studies have shown positive results in reduction of KS incidence and better KS prognosis. However, the effect of ART rollout in relation to population KS incidence is unclear. We describe the incidence of KS in sub-Saharan Africa, in four time-periods, (1) before 1980 (before HIV/AIDS era); (2) 1981–2000 (early HIV/AIDS era, limited or no ART coverage); (3) 2001–2010 (early ART coverage period); and (4) 2011–2016 (fair to good ART coverage period). We used KS incidence data available from WHO-International Agency for Research on Cancer (IARC) publications and the Africa Cancer Registry Network. National HIV prevalence and ART coverage data were derived from UNAIDS/WHO. A rapid increase in KS incidence was observed throughout sub-Saharan Africa as the HIV epidemic progressed, reaching peak incidences in Period 2 (pre-ART rollout) of 50.8 in males and 20.3 per 100 000 in females (Zimbabwe, Harare). The overall unweighted average decline in KS incidence between 2000 and 2010 and 2011–2016 was 27%, but this decline was not statistically significant across the region. ART rollout coincides with a decline in KS incidence across several regions in sub-Saharan Africa. The importance of other risk factors such as reductions in HIV incidence could not be ascertained. Highlights: In sub-Saharan Africa, there is limited evidence of a decline in Kaposi's sarcoma incidence after the rollout of antiretroviral therapy. Kaposi's sarcoma continues to be a major public health problem in terms of morbidity and mortality. The overall unweighted average decline in Kaposi's sarcoma incidence between 2000 and 2010 and 2011–2016 was 27%.